From Genes to Therapy: The Role of Candidate Gene SNP Polymorphisms in the Implementation of Personalized Medicine for Type 2 Diabetes Mellitus - Sofia, Siti; Malau, Jekmal; Damara, Dandy Satria; Purbasari, Dwi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Type 2 diabetes mellitus is a long-term metabolic disorder shaped by genetic, environmental, and lifestyle influences. Research in genomics reveals that single nucleotide polymorphisms (SNPs) in specific genes can elevate the risk of this condition and may lead to differences in how individuals react to diabetes medications, potentially positioning them as indicators for risk and treatment outcomes in personalized healthcare. This review aims to explore the contributions of SNPs in candidate genes, particularly TCF7L2 rs7903146, KCNJ11 rs5219, KCNQ1 rs2237892, SLC30A8 rs11558471, IRS1 rs1801278, CDKAL1 rs7754840, and MTNR1B rs10830963, contributes to the development of type 2 diabetes. responses to therapy, and their possible roles as clinical markers. A narrative review was carried out by searching literature on PubMed, SpringerLink, and Google Scholar using keywords like “type 2 diabetes mellitus,” “SNP,” and “pharmacogenomics.” English-language articles from 2015 to 2025 that examined connections between genetic variations and either disease risk or treatment responses in humans were included. The findings suggest that these polymorphisms largely impair beta-cell function or disrupt insulin signaling, increasing the likelihood of type 2 diabetes mellitus. Some SNPs are also tied to varied reactions to insulin-based drugs, although metformin typically demonstrates more uniform effectiveness across different genotypes. In summary, SNPs in candidate genes hold promise as tools for risk assessment and personalized treatment choices, but extensive, multi-ethnic prospective studies are essential before they can be integrated into standard clinical practice.